Aluminum alloy foil, laminate using same, and method for producing same
By controlling the content ratio of Fe, Ni and Zn in the aluminum alloy foil, the chemical solubility of the aluminum alloy foil in a weak acid environment and the uniform solubility of the aluminum alloy foil in an acid environment are solved, and a more environmentally friendly and efficient etching treatment is achieved.
Patent Information
- Application Number
- CN202380065981.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-28
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-11
AI Technical Summary
The existing aluminum foil and aluminum alloy foil are insufficient in a weak acid environment, making it difficult to obtain ideal surface properties and characteristics through etching treatment, and the harmful etching treatment liquid used at the same time poses a burden to the environment.
By controlling the content ratio of Fe, Ni and Zn in the aluminum alloy foil, the potential of the aluminum parent phase is reduced and the potential of the second phase particles is increased, thereby improving the chemical solubility in a weak acid environment and uniform solubility in an acid environment.
It achieves high chemical solubility in weak acid environments and high uniform solubility in acid environments, which reduces environmental burden and improves the efficiency of etching treatment.
Smart Images

Figure CN119816611A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum alloy foil, a laminate using the aluminum alloy foil, and methods for producing the same. Background Art
[0002] Aluminum foil or aluminum alloy foil is widely used in the fields of building materials, food packaging materials, pharmaceutical packaging materials, aluminum etching circuits, etc. as a laminate having a resin film layer and / or a coating layer laminated on one or both surfaces.
[0003] In the aluminum foils or laminates thereof, surface treatments for increasing specific surface area or imparting special surface properties, and treatments for activating the surface by dissolving and removing excess oxides, etc., are widely performed for the purpose of improving adhesion or enhancing electrochemical reactivity. As a representative of the surface treatments mentioned above, etching treatments can be cited, and as etching treatment liquids, solutions of hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), ferric chloride (FeCl3), sodium hydroxide (NaOH) or hydrofluoric acid (HF) or mixed solutions containing two or more of these solutions are used.
[0004] However, in recent years, from the perspective of protecting the global environment, there is a demand for the development of industrial materials and manufacturing technologies with low environmental impact. For this reason, in the metal industry, since there are many opportunities to use harmful substances with high environmental impact, such as strong acids and strong bases, many efforts have been made to stop the use of these harmful substances or significantly reduce their use.
[0005] The above situation also applies to the aluminum industry. The etching treatment liquid used in the manufacturing process of aluminum foil is also a hazardous substance. Therefore, the waste liquid used in the etching process needs to be properly handled as industrial waste according to its type and state. This is not only a problem from the environmental perspective, but also a heavy burden from the perspective of operation and cost.
[0006] Therefore, from the perspective of manufacturing conditions for etching aluminum foil, etc., if waste liquid treatment can be replaced with a simpler etching treatment liquid, specifically, a weak acid such as acetic acid or citric acid, the environmental burden can be reduced. However, in existing aluminum foil or aluminum alloy foil, since its chemical solubility in these weak acids may not be sufficient, there is a problem that the desired surface properties and characteristics cannot be obtained by etching with weak acids. Therefore, from the perspective of materials for etching aluminum foil, etc., if aluminum foil and aluminum alloy foil with excellent chemical solubility in weak acids can be developed, it can contribute to reducing the environmental burden.
[0007] For example, Japanese Patent Application Laid-Open No. 2008-121090 (Patent Document 1) discloses an aluminum alloy foil for printed circuits containing Si, Fe, Cu, and Ni as an aluminum alloy foil having excellent chemical solubility during etching. However, the aluminum alloy foil described in Patent Document 1 requires the use of hydrochloric acid (HCl) during etching, and has insufficient chemical solubility in weak acids, so it is not necessarily an effective solution to the problem of stopping the use of harmful substances with a large environmental burden or reducing their use.
[0008] On the other hand, in the etching process of aluminum foil and aluminum alloy foil, it is necessary to form fine shapes such as circuits, but after the etching process, undissolved parts or locally deep pits are formed in the material surface, which damages the product characteristics of the circuits, etc., and therefore must be suppressed as much as possible. Therefore, the chemical solubility of aluminum foil, etc., also has the problem of ensuring uniform solubility to suppress the formation of undissolved parts and pits during the etching process.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2008-121090 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Therefore, an object of the present invention is to provide an aluminum alloy foil having excellent chemical solubility in a weakly acidic environment and uniform solubility in an acidic environment, a laminate using the aluminum alloy foil, and a method for producing the same.
[0014] Means of solving the problem
[0015] The inventors of the present invention have conducted repeated and intensive research to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved by controlling the proportion of specific additive elements in aluminum within a specific range, lowering the potential of the aluminum matrix phase, and increasing the potential of the second phase particles distributed in the aluminum alloy foil, thereby completing the present invention.
[0016] That is, according to the present invention, there is provided an aluminum alloy foil containing Fe, Ni and Zn, with the balance comprising Al and unavoidable impurities, characterized in that, when the contents of Fe, Ni and Zn in the aluminum alloy foil are respectively set to [Fe], [Ni] and [Zn] in mass %, [Zn] is greater than 0.4 and less than 5.1, [Fe] + [Ni] is greater than 0.4 and less than 4.8, and [Fe] + [Ni] + 2×[Zn] is greater than 2.5.
[0017] In addition, [Fe] in the aluminum alloy foil is preferably 0.0001 to 3.1, [Ni] is preferably 0.0001 to 3.0, and the amount of Zn dissolved in the aluminum matrix phase in the aluminum alloy foil is preferably 0.3 mass % to 4.1 mass %.
[0018] In the present invention, the reason why [Fe] + [Ni] is controlled, and preferably [Fe] and [Ni] are controlled, is because if a certain amount of Fe and Ni are added to the aluminum alloy, second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system with a large potential difference with the aluminum matrix are formed. Then, the above-mentioned second phase particles increase the effect as cathode sites, which helps to improve the chemical solubility of the aluminum alloy foil in a weak acid environment. In addition, in the present invention, the reason why [Fe] + [Ni] + 2× [Zn] is controlled is that by adding Zn and making it solid-dissolved, the potential of the aluminum matrix is reduced, thereby using the synergistic effect with the effects of the aforementioned addition of Fe and Ni to further improve the chemical solubility of the aluminum alloy foil in a weak acid environment.
[0019] In addition, the reason why [Zn] is controlled, preferably the amount of Zn solid solution, is that most of the Zn is solid-dissolved in the aluminum matrix phase, which reduces the potential of the aluminum matrix phase. Therefore, the aluminum matrix phase in which Zn is solid-dissolved expands the potential difference between the second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system described above, which helps to improve the chemical solubility of the aluminum alloy foil in a weak acid environment. In addition, the aluminum matrix phase in which Zn is solid-dissolved can improve the uniform solubility of the aluminum alloy foil in an acidic environment.
[0020] In the present invention, the inevitable impurities include one or more elements selected from the group consisting of Si, Mn, Mg, Cu, In, Sn, Na, V, Ti, Zr, Cr, B, Ga, Bi, Pb, Sb and As, and the total content of the one or more elements is preferably 0.6% by mass or less. In particular, the content of Mn in the aluminum alloy foil is preferably 0.4% by mass or less, and the content of Mg is preferably 0.4% by mass or less. Except for Mn and Mg contained as inevitable impurities in the aluminum alloy foil, the content of each of the above elements is preferably 0.2% by mass or less.
[0021] The presence of impurities not only makes it difficult to control the chemical solubility of aluminum alloy foil in a weak acid environment and the uniform solubility in an acidic environment, but also causes defects such as cracks and pores, which often cause adverse effects. Among them, Mn and Mg are dissolved in the aluminum matrix and affect the potential of the aluminum matrix, so it is important to control their content.
[0022] In the present invention, it is preferred that the area occupancy of the second phase particles with an equivalent circle diameter of 0.1 μm or more distributed on the surface of the aluminum alloy foil is 1.7% or more as analyzed by a field emission scanning electron microscope (FE-SEM). In addition, it is preferred that the area occupancy of the second phase particles with an equivalent circle diameter of 3.0 μm or more distributed on the surface of the aluminum alloy foil is 2.0% or less.
[0023] The second phase particles are formed by particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system, but if the equivalent circle diameter is 0.1 μm or more, the potential difference with the aluminum matrix becomes large, so if the area occupancy rate of the aluminum alloy foil surface is not controlled, the desired chemical solubility of the aluminum alloy foil in a weak acid environment cannot be obtained. On the other hand, if the equivalent circle diameter is 3.0 μm or more, coarse particles become the cause of defects such as cracks and pores, so if the area occupancy rate of the aluminum alloy foil surface is not controlled, the rolling processability is reduced.
[0024] In the present invention, when the aluminum alloy foil is required to have appropriate strength and easy workability, the thickness thereof is preferably 5 μm or more and 300 μm or less.
[0025] Furthermore, the aluminum alloy foil of the present invention may be configured as a laminate by forming a resin film layer and / or a coating layer on one or both surfaces thereof depending on the intended use.
[0026] In the present invention, the above-mentioned aluminum alloy foil having high chemical solubility in a weakly acidic environment and high uniform solubility in an acidic environment can be manufactured by a manufacturing method comprising the following steps: a step of preparing a molten aluminum alloy, the molten aluminum alloy containing Fe, Ni and Zn, with the balance consisting of Al and unavoidable impurities, wherein when the contents of Fe, Ni and Zn in the molten aluminum alloy are respectively set to [Fe], [Ni] and [Zn] in mass %, [Zn] is adjusted to be greater than 0.4 and less than 5.1, [Fe] + [Ni] is adjusted to be greater than 0.4 and less than 4.8, and [Fe] + [Ni] + 2× [Zn] is adjusted to be greater than 2.5; a casting step of casting the molten metal to obtain a casting; and a rolling step of obtaining the aluminum alloy foil by cold rolling the casting.
[0027] The laminate using the aluminum alloy foil of the present invention can be produced by a production method comprising the steps of: preparing the aluminum alloy foil obtained by the above production method; and laminating a resin film layer and / or a coating layer on one or both surfaces of the aluminum alloy foil.
[0028] Effects of the Invention
[0029] The aluminum alloy foil of the present invention and the laminated body using the aluminum alloy foil have high chemical solubility in a weak acid environment and high uniform solubility in an acidic environment. In addition, the manufacturing method of the present invention can manufacture the aluminum alloy foil and the laminated body using the aluminum alloy foil having the above-mentioned characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1A This is a SEM photograph (×1000 times) of the surface of the aluminum alloy foil of Example 4, in which the area occupancy of second phase particles having an equivalent circle diameter of 0.1 μm or more is 6.38%.
[0031] Figure 1B This is a SEM photograph (×1000 times) of the surface of the aluminum alloy foil of Example 12, in which the area occupancy of second phase particles having an equivalent circle diameter of 3.0 μm or more was 1.69%.
[0032] Figure 2A This is a SEM photograph (×1000 times) of the surface of the aluminum alloy foil of Comparative Example 6, in which the area occupancy of second phase particles having an equivalent circle diameter of 0.1 μm or more is 3.85%.
[0033] Figure 2B This is a SEM photograph (×1000 times) of the surface of the aluminum alloy foil of Comparative Example 9, in which the area occupancy of the second phase particles having an equivalent circle diameter of 3.0 μm or more was 7.55%.
[0034] Figure 3 This is a scatter plot showing the relationship between ([Fe] + [Ni] + 2×[Zn]) and chemical solubility in a weak acid environment (expressed as “weak acid solubility” in the figure).
[0035] Figure 4 This is a scatter plot of the relationship between [Zn] and uniform solubility in an acidic environment (represented as "uniform solubility" in the figure). DETAILED DESCRIPTION
[0036] Hereinafter, an aluminum alloy foil, a laminate using the aluminum alloy foil and a method for producing the same according to an embodiment of the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and various modifications can be made without departing from the technical concept of the present invention.
[0037] 1.Aluminum alloy foil
[0038] (1) Aluminum alloy foil
[0039] The aluminum alloy foil of the present invention contains iron (Fe), nickel (Ni), zinc (Zn), and the balance contains aluminum (Al) and inevitable impurities. The aluminum alloy foil may contain inevitable impurities within a range that does not impair the chemical solubility in a weak acid environment, the uniform solubility in an acid environment, the rolling processability, the etching property, and the manufacturability of the aluminum alloy foil.
[0040] The inevitable impurities include one or more elements selected from the group consisting of silicon (Si), manganese (Mn), magnesium (Mg), copper (Cu), indium (In), tin (Sn), sodium (Na), vanadium (V), titanium (Ti), zirconium (Zr), chromium (Cr), boron (B), gallium (Ga), bismuth (Bi), lead (Pb), antimony (Sb) and arsenic (As). In addition, in the present invention, the content of aluminum (Al) contained in the aluminum alloy foil is preferably 89.0 mass % or more.
[0041] (2) Composition of aluminum alloy foil
[0042] <Iron (Fe)>
[0043] If a certain amount of Fe is added to an aluminum alloy, Al-Fe based second phase particles and / or Al-Fe-Ni based second phase particles are formed together with Ni. The second phase particles containing Fe act as cathode sites with a higher potential than the aluminum matrix, improving the chemical solubility of the aluminum alloy foil in a weak acid environment.
[0044] If the content of Fe is higher than 3.1% by mass, the material strength increases due to precipitation strengthening, and defects such as edge cracks occur, which hinder rolling processability. In addition, coarse second phase particles are easily formed during casting, which not only hinders rolling processability, but also hinders uniform surface formation in etching treatment, and becomes a cause of defects such as pores in the process of manufacturing aluminum alloy foil with a thickness of less than 10 μm. The lower limit of the content of Fe is not particularly limited, but is usually about 0.0001% by mass. In order to make the content of Fe lower than 0.0001% by mass, it is necessary to repeat the three-layer electrolysis method, etc., and the manufacturing cost is significantly increased. Therefore, the Fe content in the aluminum alloy foil is preferably 0.0001% by mass and 3.1% by mass, more preferably 0.0001% by mass and 1.8% by mass, and then further preferably 0.0001% by mass and 1.5% by mass.
[0045] <Nickel(Ni)>
[0046] If a certain amount of Ni is added to an aluminum alloy, Al-Ni based second phase particles are formed and / or Al-Fe-Ni based second phase particles are formed together with Fe. The potential difference between the second phase particles containing Ni and the aluminum matrix is particularly large, which increases the effect of the cathode site. Therefore, if Ni is added to an aluminum alloy, the chemical solubility of the aluminum alloy foil in a weak acid environment is improved.
[0047] If the content of Ni is higher than 3.0% by mass, the material strength increases due to precipitation strengthening, and defects such as edge cracks occur and hinder rolling processability. In addition, coarse second phase particles are easily formed during casting, which not only hinders rolling processability, but also hinders uniform surface formation in etching treatment, and becomes the cause of defects such as pores in the process of manufacturing aluminum alloy foil with a thickness of less than 10 μm. The lower limit of the content of Ni is not particularly limited, but is usually about 0.0001% by mass. In order to make the content of Ni lower than 0.0001% by mass, it is necessary to repeat the three-layer electrolysis method, etc., and the manufacturing cost is significantly increased. Therefore, the Ni content in the aluminum alloy foil is preferably 0.0001% by mass and less than 3.0% by mass, more preferably 0.0001% by mass and less than 2.6% by mass, and then further preferably 0.0001% by mass and less than 1.8% by mass.
[0048] <Zinc (Zn)>
[0049] If a certain amount of Zn is added to the aluminum alloy, most of it will be dissolved in the aluminum matrix phase, and the potential of the aluminum matrix phase will be reduced. As a result, the potential difference between the second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system and the aluminum matrix phase will be expanded, so that the chemical solubility of the aluminum alloy foil in a weak acid environment is improved, and the uniform solubility of the aluminum alloy foil in an acidic environment is improved.
[0050] If the Zn content is less than 0.4% by mass, the amount of Zn solid solution in the aluminum matrix phase is reduced, the potential reduction effect of the aluminum matrix phase is insufficient, and the chemical solubility of the aluminum alloy foil in a weak acid environment and the uniform solubility of the aluminum alloy foil in an acidic environment are impaired. On the other hand, if the Zn content is further increased and is higher than 2.1% by mass, although the uniform solubility of the aluminum alloy foil remains unchanged, the chemical solubility is impaired. If the Zn content is higher than 5.1% by mass, solid solution strengthening leads to increased material strength, which hinders rolling processability. Therefore, the Zn content in the aluminum alloy foil is preferably 0.4% by mass or more and 5.1% by mass or less, more preferably 0.5% by mass or more and 2.9% by mass or less, and then further preferably 0.75% by mass or more and 2.1% by mass or less.
[0051] <[Fe]+[Ni]>
[0052] If a certain amount of Fe and Ni is added to the aluminum alloy, Al-Fe, Al-Ni and / or Al-Fe-Ni second phase particles are formed. These second phase particles have a large potential difference with the aluminum matrix, and their effect as cathode sites is enhanced, thereby improving the chemical solubility of the aluminum alloy foil in a weak acid environment.
[0053] When the contents of Fe and Ni in the aluminum alloy foil are respectively set to [Fe] and [Ni] in mass %, if [Fe] + [Ni] is less than 0.4, the number of second phase particles is reduced, and the sufficient effect as a cathode site relative to the aluminum matrix cannot be achieved, and the chemical solubility of the aluminum alloy foil in a weak acid environment is insufficient. If [Fe] + [Ni] is higher than 4.8, the material strength increases due to precipitation strengthening, and defects such as edge cracks occur, which hinder rolling workability. Therefore, [Fe] + [Ni] is preferably 0.4 or more and 4.8 or less, more preferably 0.9 or more and 4.0 or less, and further preferably 1.4 or more and 2.9 or less.
[0054] <[Fe]+[Ni]+2×[Zn]>
[0055] If a certain amount of Fe and Ni is added to the aluminum alloy, Al-Fe, Al-Ni and / or Al-Fe-Ni second phase particles are formed. These second phase particles have a large potential difference with the aluminum matrix, and their effect as cathode sites is enhanced, thereby improving the chemical solubility of the aluminum alloy foil in a weak acid environment.
[0056] In addition, if a certain amount of Zn is added to the aluminum alloy, most of it will be dissolved in the aluminum matrix phase, which has the effect of lowering the potential of the aluminum matrix phase. As a result, the potential difference between the second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system and the aluminum matrix phase in which Zn is dissolved is expanded, further improving the chemical solubility of the aluminum alloy foil in a weak acid environment.
[0057] When the contents of Fe, Ni and Zn in the aluminum alloy foil are respectively [Fe], [Ni] and [Zn] in mass %, if [Fe] + [Ni] + 2 × [Zn] is less than 2.5, the synergistic effect of the effects of adding Fe and Ni and the effect of adding Zn is insufficient, and the chemical solubility of the aluminum alloy foil in a weak acid environment is insufficient. Therefore, [Fe] + [Ni] + 2 × [Zn] is preferably 2.5 or more, more preferably 2.85 or more, and further preferably 2.95 or more.
[0058] <Zn solid solution content>
[0059] Zn existing in the aluminum matrix phase in a solid solution state helps to form a uniform surface during etching, that is, helps to suppress the occurrence of undissolved parts. The larger the amount of Zn solid solution, the lower the potential of the aluminum matrix phase, and the more uniform solubility of the aluminum alloy foil in an acidic environment is improved.
[0060] If the Zn solid solution amount is higher than 4.1% by mass, solid solution strengthening leads to an increase in material strength, which hinders rolling workability. If the Zn solid solution amount is lower than 0.3% by mass, the effect of reducing the aluminum matrix potential is insufficient, and the uniform solubility of the aluminum alloy foil in an acidic environment is impaired. Therefore, in the aluminum alloy foil, the Zn solid solution amount solidified in the aluminum matrix is preferably 0.3% by mass or more and 4.1% by mass or less, more preferably 0.4% by mass or more and 2.7% by mass or less, and then further preferably 0.5% by mass or more and 1.5% by mass or less.
[0061] <Impurities>
[0062] In addition to the above-mentioned elements, the aluminum alloy foil may also contain one or more elements selected from the group consisting of Si, Mn, Mg, Cu, In, Sn, Na, V, Ti, Zr, Cr, B, Ga, Bi, Pb, Sb and As as inevitable impurities. Preferably, the total content of the one or more elements is 0.6% by mass or less. In particular, it is preferred that the content of Mn in the aluminum alloy foil is 0.4% by mass or less, and the content of Mg is 0.4% by mass or less. Except for Mn and Mg contained in the aluminum alloy foil as inevitable impurities, it is preferred that the content of each of the above elements is 0.2% by mass or less.
[0063] <Impurities>
[0064] If a certain amount of Si is added to the aluminum alloy, the chemical solubility of the aluminum alloy foil in a weak acid environment is improved. However, if the Si content is higher than 0.2 mass %, the coarsening of the second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system is promoted, and the rolling workability and the uniform solubility of the aluminum alloy foil in an acidic environment are impaired.
[0065] The lower limit of the Si content is not particularly limited, but is generally about 0.0001 mass %. In order to make the Si content lower than 0.0001 mass %, it is necessary to repeat the three-layer electrolysis method, etc., which significantly increases the manufacturing cost. Therefore, the Si content in the aluminum alloy foil is preferably 0.0001 mass % or more and 0.2 mass % or less, more preferably 0.0001 mass % or more and 0.15 mass % or less, and then further preferably 0.0001 mass % or more and 0.1 mass % or less.
[0066] (Mn)
[0067] If a certain amount of Mn is added to an aluminum alloy, most of it will be dissolved in the aluminum matrix, but a part of it will form Al-Mn system, or form Al-Mn-Fe system, Al-Mn-Ni system, Al-Mn-Si system, Al-Mn-Fe-Ni system, Al-Mn-Ni-Si system, Al-Mn-Si-Fe system or Al-Mn-Fe-Ni-Si system with Fe, Ni and Si. If the content of Mn exceeds 0.4% by mass, the Mn content in the second phase particles and the amount of Mn dissolved in the aluminum matrix increase, the potential of the second phase particles approaches the potential of the aluminum matrix, and the effect of the second phase particles as cathode sites decreases. As a result, the chemical solubility of the aluminum alloy foil in a weak acid environment decreases.
[0068] The lower limit of the content of Mn is not particularly limited, but is generally about 0.0001 mass %. In order to make the content of Mn lower than 0.0001 mass %, it is necessary to repeat the three-layer electrolysis method, etc., which significantly increases the manufacturing cost. Therefore, the Mn content in the aluminum alloy foil is preferably 0.0001 mass % or more and 0.4 mass % or less, more preferably 0.0001 mass % or more and 0.2 mass % or less, and then further preferably 0.0001 mass % or more and 0.1 mass % or less.
[0069] (Mg)
[0070] If a certain amount of Mg is added to an aluminum alloy, a part of it will be dissolved in the aluminum matrix. If the Mg content is higher than 0.4 mass%, Mg will be concentrated in the oxide film formed on the surface of the aluminum alloy material, and the oxide film will easily have defects. Such oxide film defects, for example, become a factor causing delamination at the bonding interface of a laminated body formed by laminating an aluminum alloy foil and a resin film. In addition, the addition of Mg has the effect of reducing the chemical solubility of the aluminum alloy foil and improving the corrosion resistance.
[0071] The lower limit of the Mg content is not particularly limited, but is generally about 0.0001 mass %. In order to make the Mg content lower than 0.0001 mass %, it is necessary to repeat the three-layer electrolysis method, etc., which significantly increases the manufacturing cost. Therefore, the Mg content in the aluminum alloy foil is preferably 0.0001 mass % or more and 0.4 mass % or less, more preferably 0.0001 mass % or more and 0.2 mass % or less, and further preferably 0.0001 mass % or more and 0.1 mass % or less.
[0072] (Cu)
[0073] If a certain amount of Cu is added to an aluminum alloy, part of it will be dissolved in the aluminum matrix phase. If the Cu content exceeds 0.2 mass %, the amount of Cu dissolved in the aluminum matrix phase will increase, and the solid solution strengthening will increase the material strength, which may hinder rolling workability.
[0074] The lower limit of the content of Cu is not particularly limited, but is generally about 0.0001 mass %. In order to make the content of Cu lower than 0.0001 mass %, in addition to the three-layer electrolysis method, it is also necessary to repeat the fractional crystallization method, etc., which significantly increases the manufacturing cost. Therefore, the Cu content in the aluminum alloy foil is preferably 0.0001 mass % or more and 0.2 mass % or less, more preferably 0.0001 mass % or more and 0.15 mass % or less, and then further preferably 0.0001 mass % or more and 0.1 mass % or less.
[0075] (In, Sn)
[0076] If a certain amount of In and / or Sn is added to an aluminum alloy, most of them are dissolved in the aluminum matrix phase, which has the effect of reducing the potential of the aluminum matrix phase. As a result, the potential difference between the second phase particles of the Al-Fe system, Al-Ni system and / or Al-Fe-Ni system and the aluminum matrix phase in which In and / or Sn are dissolved is enlarged, and the chemical solubility of the aluminum alloy foil in a weak acid environment is improved. If the addition amount of In and / or Sn is higher than 0.2 mass%, the potential reduction effect of the aluminum matrix phase is saturated and the rolling processability is hindered. Therefore, the In content in the aluminum alloy foil is preferably greater than 0.0001 mass% and less than 0.2 mass%, and the Sn content is preferably greater than 0.0001 mass% and less than 0.2 mass%.
[0077] <Area occupancy of second phase particles with an equivalent circle diameter of 0.1 μm or more distributed on the surface of the aluminum alloy foil>
[0078] If the above elements are added to aluminum, second phase particles are generated in the aluminum matrix. Specifically, they are second phase particles of Al-Fe, Al-Ni and / or Al-Fe-Ni. However, these second phase particles have a large potential difference with the aluminum matrix and function as cathode sites. As a result, the chemical solubility of aluminum alloy foil in a weak acid environment is improved.
[0079] In the aluminum alloy foil, if the area occupancy rate of the second phase particles with an equivalent circle diameter of 0.1 μm or more distributed on the surface is less than 1.7%, the sufficient effect as a cathode site cannot be obtained, and the chemical solubility of the aluminum alloy foil in a weak acid environment is insufficient. Therefore, on the surface of the aluminum alloy foil, the area occupancy rate of the second phase particles with an equivalent circle diameter of 0.1 μm or more is preferably 1.7% or more, more preferably 4.1% or more, and further preferably 5.6% or more.
[0080] <Area occupancy of second phase particles with an equivalent circle diameter of 3.0 μm or more distributed on the surface of the aluminum alloy foil>
[0081] When the above-mentioned elements are added to aluminum, second phase particles are generated in the aluminum matrix. Specifically, second phase particles of Al-Fe, Al-Ni and / or Al-Fe-Ni are generated. However, coarse second phase particles with an equivalent circle diameter of 3.0 μm or more hinder rolling workability.
[0082] In aluminum alloy foil, if the area occupancy rate of the second phase particles with an equivalent circle diameter of 3.0 μm or more distributed on the surface exceeds 2.0%, defects such as edge cracks occur, which hinders rolling workability. Therefore, on the surface of aluminum alloy foil, the area occupancy rate of the second phase particles with an equivalent circle diameter of 3.0 μm or more is preferably 2.0% or less, more preferably 0.8% or less, and further preferably 0.5% or less.
[0083] <Thickness of aluminum alloy foil>
[0084] From the viewpoint of strength and manufacturability, the thickness of the aluminum alloy foil of the present invention is preferably 5 μm or more. In addition, from the viewpoint of lightweighting the aluminum alloy foil, the thickness of the aluminum alloy foil is preferably 300 μm or less. In addition, the thickness of the aluminum alloy foil is more preferably 5 μm or more and 200 μm or less. In order to control the thickness of the aluminum alloy foil within the above range, casting and rolling can be performed in accordance with conventional methods. In addition, for the purpose of homogenizing the aluminum alloy foil, heat treatment can also be appropriately performed.
[0085] 2. Method for manufacturing aluminum alloy foil
[0086] The method for producing an aluminum alloy foil of the present invention is characterized in that it comprises a step of rolling a cast body (hereinafter also referred to as an "ingot"), wherein the cast body contains Fe, Ni and Zn, and the balance contains Al and unavoidable impurities, and when the contents of Fe, Ni and Zn are respectively defined as [Fe], [Ni] and [Zn] in mass %, [Zn] is greater than 0.4 and less than 5.1, [Fe] + [Ni] is greater than 0.4 and less than 4.8, and [Fe] + [Ni] + 2×[Zn] is greater than 2.5.
[0087] The ingot having the above composition can be obtained, for example, by melting an aluminum ingot, casting a molten metal whose composition has been adjusted by adding Fe or an Al-Fe master alloy, Ni or an Al-Ni master alloy, and Zn or an Al-Zn master alloy, and solidifying the molten metal. The casting method is not particularly limited, and a known method such as semi-continuous casting, continuous casting, or mold casting can be used.
[0088] The obtained ingot may be subjected to heat treatment for the purpose of homogenization, etc. The homogenization heat treatment is preferably performed under the conditions of a heating temperature of 400° C. to 630° C. and a heating time of 1 hour to 20 hours, for example.
[0089] As the rolling method, a well-known rolling method can be used without particular limitation. However, from the viewpoint of easily adjusting the thickness of the aluminum alloy foil, it is preferred to provide a cold rolling process after the hot rolling process. In addition, the number of hot rolling times in the hot rolling process and the number of cold rolling times in the cold rolling process can be appropriately set according to the final thickness of the aluminum alloy foil as the target.
[0090] When cold rolling is performed multiple times in the cold rolling process, intermediate annealing is preferably performed. In this case, the cold rolling process is preferably performed in the order of one or more cold rollings, intermediate annealing, and one or more cold rollings. Intermediate annealing is preferably performed under the following conditions: the annealing temperature is 50° C. or more and 500° C. or less, and the annealing time is 1 second or more and 20 hours or less. By performing intermediate annealing, the thickness of the aluminum alloy foil can be easily adjusted.
[0091] After the cold rolling process, a heat treatment process may be further provided to perform a heat treatment at a temperature of 50° C. to 450° C. for about 1 second to 50 hours. By providing a heat treatment process, rolling oil remaining on the surface of the aluminum alloy foil can be removed to improve wettability, and the structure of the aluminum alloy foil can be homogenized to adjust mechanical properties.
[0092] 3. Laminated body using aluminum alloy foil and method for producing the same
[0093] <Laminate using aluminum alloy foil>
[0094] The aluminum alloy foil of the present invention can also be formed into a laminate by laminating a resin film layer and / or a coating layer on one or both sides thereof in whole or in part. In addition, when laminating both a resin film layer and a coating layer on one or both sides of the aluminum alloy foil in whole or in part, it is preferred to laminate the coating layer on the aluminum alloy foil and laminate the resin film layer on the coating layer.
[0095] Because the aluminum alloy foil of the present invention has excellent chemical solubility in a weak acid environment, even if a laminated body is formed in which a resin film layer and / or a coating layer is laminated on both the surface and back sides of the aluminum alloy foil, when immersed in a weak acid, the aluminum alloy foil layer can be dissolved from the end surface of the laminated body, and the resin film layer and / or the coating layer can be easily separated from the aluminum alloy foil layer.
[0096] When the laminate is formed using aluminum alloy foil, the number of layers and the order of layers of resin film layers and coating layers laminated on the aluminum alloy foil can be appropriately set according to the use of the laminate, etc., and there is no particular limitation. In addition, from the viewpoint of strength, the overall thickness of the laminate is preferably 6 μm or more, and from the viewpoint of lightweight, it is preferably 301 μm or less, and if both viewpoints are taken into consideration, it is further preferably 10 μm or more and 201 μm or less.
[0097] <Resin film (layer)>
[0098] As the resin film used for the resin film layer laminated on the aluminum alloy foil, films made of known resins can be widely used without particular limitation. Specifically, films made of one or more resins selected from polyethylene, polypropylene, polybutylene, polyethylene terephthalate, polyethylene naphthalate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyamide, polyimide and vinyl chloride can be used.
[0099] The thickness of the resin thin film layer laminated on the aluminum alloy foil may be appropriately set in consideration of the thickness of the aluminum alloy foil and the thickness of the coating layer described below so that the overall thickness of the laminate falls within the above numerical range.
[0100] When the resin film layer is laminated on the aluminum alloy foil, as a method for bonding the two, a wide range of known bonding and laminating methods can be adopted without particular limitation. Specifically, dry lamination method using a two-liquid curing adhesive such as polyester polyurethane system or polyester system, coextrusion method, extrusion coating method, extrusion lamination method, heat sealing method, or heat lamination method using an anchoring agent can be cited.
[0101] <Paint (layer)>
[0102] As the coating layer of the aluminum alloy foil, an inorganic coating layer formed of titanium oxide, silicon oxide, zirconium oxide, or chromium composition, or a resin coating layer formed of acrylic, polycarbonate, silicone resin, or fluororesin can be used.
[0103] In addition, the coating layer of the aluminum alloy foil can be surface-modified by plasma treatment, fatty acid, silane coupling agent, etc., or a modified substance formed by acid and / or base, etc. can be used appropriately, and there is no particular limitation. The thickness of the coating layer can also be appropriately set so that the overall thickness of the laminate is within the above-mentioned numerical range and the thickness of the aluminum alloy foil and the resin film layer is taken into consideration.
[0104] As a method for forming a coating layer on an aluminum alloy foil, any known method can be used, such as a method of coating using a coating agent such as spin coating, rod coating, flow coating, dip coating or die coating, or a coating method in which two or more coating methods are combined. In addition, a heat treatment for drying or reaction may be performed after coating.
[0105] In addition, as other methods for forming the coating layer, surface treatment methods such as ion plasma treatment, ion plating treatment, sputtering treatment, evaporation treatment or plating treatment can be listed, or a surface treatment method combining two or more of the above surface treatment methods. In addition, a coating layer lamination method combining one or more of the above coating methods and one or more of the surface treatment methods can also be used.
[0106] Example
[0107] Hereinafter, examples and comparative examples are given to further clarify the features of the present invention.
[0108] Aluminum alloys having the compositions shown in Tables 1 and 2 were melted and cast by a die casting method at a cooling rate of 1°C / sec or more and 15°C / sec or less to obtain ingots of aluminum alloys of Examples and Comparative Examples. The obtained ingots of aluminum alloys were then heat treated at 530°C for 5 hours. Cold rolling was then performed multiple times until the thickness was 50 μm to produce aluminum alloy foils of Examples 1 to 45 shown in Table 1 and aluminum alloy foils of Comparative Examples 1 to 16 shown in Table 2.
[0109] Table 1
[0110]
[0111] Table 2
[0112]
[0113] <Measurement of the composition of aluminum alloy foil>
[0114] The analysis of each component in the aluminum alloy foil was performed as follows: 1.00 g of each aluminum alloy foil was weighed and measured using an inductively coupled plasma emission spectrometer (manufactured by Shimadzu Corporation: ICPS-8100). The results are shown in Tables 1 and 2. The detection limit of each element in the above measurement method is 0.01 mass %, so in Tables 1 and 2, elements below the detection limit are all shown as 0.00%.
[0115] <Calculation of the equivalent circle diameter of the second phase particles distributed on the surface of aluminum alloy foil and measurement of the area occupancy>
[0116] The calculation of the equivalent circle diameter of the second phase particles distributed on the surface of the aluminum alloy foil and the measurement of the area occupancy were performed by the following method. That is, as the measurement sample, the aluminum alloy foil of each embodiment and each comparative example whose surface was mirror-finished was used, and the mirror-finishing was performed using a polishing cloth (MD-Mol and MD-Nap manufactured by Struers Co., Ltd.) and a diamond suspension (DiaPro Mol R 3μm and DiaProNap R 1μm manufactured by Struers Co., Ltd.).
[0117] The area occupancy of the second phase particles on the surface of each sample was measured using the backscattered electron image obtained by observing the surface of each sample using a field emission scanning electron microscope (FE-SEM). Specifically, first, 10 rectangular fields of view were randomly selected from the backscattered electron images of each sample surface. The range of each rectangular field of view was 0.01069 mm. 2 The backscattered electron images of each rectangular field of view were binarized using image processing software (WinROOF2021, manufactured by Mitani Shoji Co., Ltd.) with a brightness of 100 or more and 255 or less, and the second phase particles with an equivalent circle diameter of 0.1 μm or more and the second phase particles with an equivalent circle diameter of 3.0 μm or more were extracted.
[0118] Using the aforementioned image processing software, the area occupancy of the second phase particles within the measurement surface (rectangular field of view) was calculated for the second phase particles with an equivalent circle diameter of 0.1 μm or more and the second phase particles with an equivalent circle diameter of 3.0 μm or more extracted in this way, and the average value of the above calculation results obtained from 10 rectangular fields of view was taken as the area occupancy of the second phase particles. The results are shown in Tables 1 and 2.
[0119] Figure 1A , as an example of an SEM photograph before binarization, a SEM photograph of the surface of the aluminum alloy foil of Example 4 in which the area occupancy rate of second phase particles having an equivalent circle diameter of 0.1 μm or more is 6.38% is shown. Figure 1B , a SEM photograph of the surface of the aluminum alloy foil of Example 12 is shown, in which the area occupancy rate of the second phase particles having an equivalent circle diameter of 3.0 μm or more is 1.69%. Figure 2A , a SEM photograph of the surface of the aluminum alloy foil of Comparative Example 6 showing that the area occupancy rate of the second phase particles having an equivalent circle diameter of 0.1 μm or more is 3.85% is shown. Figure 2B , a SEM photograph of the surface of the aluminum alloy foil of Comparative Example 9 is shown, in which the area occupancy rate of the second phase particles having an equivalent circle diameter of 3.0 μm or more is 7.55%.
[0120] <Evaluation of chemical solubility of aluminum alloy foil in weak acid environment>
[0121] The chemical solubility of the aluminum alloy foil surface in a weakly acidic environment was evaluated by the following method. That is, the aluminum alloy foil of each embodiment and each comparative example was cut into a size of 40 mm × 40 mm, and as a pretreatment, it was immersed in a 1 mass % sodium hydroxide solution at 35°C and 60 seconds, and then immersed in 30 mass % nitric acid at 25°C and 60 seconds. The aluminum alloy foil after the above treatment was used as a test piece for measurement. Each test piece was immersed in an aqueous solution containing 3 mass % sodium chloride and 3 mass % acetic acid at 40°C and 2700 seconds, and the mass before and after immersion was measured, thereby calculating the dissolution loss per unit surface area of each test piece. As a result, the dissolution loss per unit surface area of the test piece was 2.8μg / mm 2 The above results were evaluated as having sufficient chemical solubility.
[0122] <Evaluation of uniform solubility in an acidic environment>
[0123] The evaluation of the uniform solubility of the aluminum alloy foil surface in an acidic environment is carried out by the following method. That is, the aluminum alloy foil of each embodiment and each comparative example is cut into a size of 10 mm × 40 mm, and as a pretreatment, it is immersed in a 1% by mass sodium hydroxide solution at 35°C and 60 seconds, and then immersed in 30% by mass nitric acid at 25°C and 60 seconds. The aluminum alloy foil treated above is used as a test piece for measurement. In a manner where the dissolution loss of each test piece is greater than 0.0025g and less than 0.0029g, it is immersed in a 35°C aqueous solution containing 8% by mass hydrochloric acid and 4% by mass aluminum chloride for a specified time. The surface of each test piece (aluminum alloy foil) after immersion is observed with a laser microscope, and the maximum height roughness Sz is measured accordingly.
[0124] The laser microscope was used to observe the unevenness of the test piece surface. The laser microscope VK-X3000 manufactured by KEYENCE Co., Ltd. was used to measure the shape by laser confocal in a rectangular field of view of 285.727μm×214.295μm. The VK-X3000 multi-file analysis application manufactured by KEYENCE Co., Ltd. was used to measure the maximum height roughness Sz of the test piece. Specifically, first, for the obtained shape data, the surface shape correction was performed to remove the waviness with a cutoff value of 0.5mm, and then the height cutoff level correction was performed with a cutoff level of 50 to remove the noise component of the laser light reflection.
[0125] The maximum height roughness Sz of each test piece is measured using the VK-X3000 multi-file analysis application manufactured by KEYENCE Co., Ltd. according to the morphological parameters in the surface properties parameters of ISO25178. The maximum height roughness Sz of each test piece used for evaluation is the average value of the calculation results obtained from 5 rectangular fields of view. The maximum height roughness Sz of the test piece below 7.1μm is evaluated as having sufficient uniform solubility. The results are shown in Tables 1 and 2.
[0126] <Evaluation of rolling workability>
[0127] The rolling workability of the aluminum alloy foil was evaluated by the following method. That is, in the cold rolling process, when the ingots (cast bodies) of each embodiment and each comparative example having the composition shown in Table 1 and Table 2 were cold rolled to a specified thickness, the rolling workability of the sample (aluminum alloy foil) whose material width was reduced by less than 3% of the material width before the start of cold rolling due to edge cracking was evaluated as "A", the rolling workability of the sample with a width of more than 3% and less than 10% was evaluated as "B", the rolling workability of the sample with a width of more than 10% and less than 25% was evaluated as "C", and the rolling workability of the sample with a width of more than 25% was evaluated as "F". The results are shown in Tables 1 and 2.
[0128] <Measurement of Zn Solid Solution Amount in Aluminum Alloy Foil>
[0129] The measurement of the Zn solid solution amount in the aluminum alloy foil is carried out by the following method. That is, 0.1 g of the sample is extracted from each aluminum alloy foil, and only the aluminum matrix in the aluminum alloy foil is dissolved with phenol, and filtered with a membrane filter with a pore size of 0.1 μm (manufactured by Toyo Filter Paper Co., Ltd.: H100A047A), thereby collecting the second phase particles. The second phase particles are dissolved with acid and alkali, and the amount of Zn precipitation is obtained using an inductively coupled plasma emission spectrometer (manufactured by Shimadzu Corporation: ICPS-8100). The Zn solid solution amount is obtained by subtracting the above-mentioned Zn precipitation amount from the Zn content of the entire aluminum alloy foil. The results are shown in Table 3.
[0130] <Measurement of the spontaneous potential and cathodic polarization curve of aluminum alloy foil>
[0131] In order to investigate the influence of the composition of aluminum alloy foil, the area occupancy of the second phase particles, and the amount of Zn solid solution on chemical solubility, the natural potential and the absolute value of the cathode current density were measured up to 1 mA / cm 2 The potential at time.
[0132] Specifically, the above-mentioned potential measurement was carried out by the following method at a temperature of 25° C. and under the condition of being open to the atmosphere. In addition, the aluminum alloy foil of each embodiment and each comparative example was cut into a size of 15 mm×17 mm, and as a pretreatment, it was immersed in a 1% by mass sodium hydroxide solution at 35° C. for 15 seconds, and then immersed in 30% by mass nitric acid at 25° C. for 30 seconds, and the aluminum alloy foil subjected to the above treatment was used as a test piece.
[0133] The potential was measured using a corrosion cell VM1 manufactured by EC FRONTIER Co., Ltd. As the test solution, a 25°C, pH 5.5, 5 mass% NaCl aqueous solution was used, as the counter electrode, a platinum-coated titanium rod (EC FRONTIER Co., Ltd.: counter electrode VM1-5) was used, as the reference electrode, an Ag / AgCl reference electrode RE-1A manufactured by EC FRONTIER Co., Ltd. was used, and as the working electrode sample holder, a sample holder VM1-3 manufactured by EC FRONTIER Co., Ltd. was used, and the electrode potential was measured by the three-electrode method. In addition, there was a 1cm area on the sample holder. 2 The circular sample window is provided, and the surface of the test piece exposed from the sample window serves as a working electrode.
[0134] The absolute value of the natural potential and cathode current density reaches 1mA / cm 2 To measure the potential at the time of the test, first immerse the working electrode, counter electrode and reference electrode mentioned above in the above test solution and let it stand for 600 seconds. During this period, measure the electrode potential at a sampling interval of 10 seconds, and take the average value of 60 points as the "natural potential" of the aluminum alloy foil. Next, use a constant potential meter (manufactured by Hokuto Denko Co., Ltd.: Electrochemical Measurement System HZ-7000 Series) to scan from the natural potential of each test piece to -1500mV in a decreasing direction at a scanning speed of 0.5mV / s, and measure the cathode polarization curve. In this cathode polarization curve, the absolute value of the current density is read to reach 1mA / cm 2 The electrode potential at the time of the cathode current density is taken as the absolute value of the cathode current density of the aluminum alloy foil reaching 1 mA / cm 2 The results are shown in Table 3.
[0135] Table 3
[0136]
[0137] According to Table 3, for example, in an aluminum alloy foil, if the amount of Zn solid solution increases and the potential of the aluminum matrix phase is low, the natural potential in the measurement is also low. In addition, for example, when the contents of Fe and Ni in the aluminum alloy foil are set as [Fe] and [Ni] in mass %, if the increase of [Fe] + [Ni] or the increase of the area occupancy of the second phase particles with an equivalent circle diameter of 0.1 μm or more leads to an increase in the portion that acts as a cathode site relative to the aluminum matrix phase, then a smaller potential scan reaches 1 mA / cm 2 Therefore, it can be judged that the absolute value of the cathode current density of the aluminum alloy foil reaches 1mA / cm 2 The larger the "potential at that time", that is, the closer it is to the natural potential, the more parts act as cathode sites.
[0138] <Investigation>
[0139] The aluminum alloy foils of Examples 1 to 45 shown in Table 1 have a chemical solubility (dissolution loss per unit surface area) of 2.8 μg / mm in a weakly acidic environment. 2 As described above, the uniform solubility in an acidic environment (maximum height roughness Sz after acid treatment) is less than 7.1 μm, and the evaluation of rolling processability during cold rolling is "A", "B" or "C" (see Table 1). It can be seen that all aluminum alloy foils have excellent chemical solubility in a weakly acidic environment, excellent uniform solubility in an acidic environment, and excellent rolling processability.
[0140] On the other hand, the aluminum alloy foils of Comparative Examples 1 to 16 shown in Table 2 have a chemical solubility (dissolution loss per unit surface area) in a weakly acidic environment of less than 2.8 μg / mm 2 , or the uniform solubility in an acidic environment (maximum height roughness Sz after acid treatment) is greater than 7.1μm, or the evaluation of rolling workability during cold rolling is "F" (see Table 2). Therefore, it can be seen that at least one of the evaluations of chemical solubility in a weakly acidic environment, uniform solubility in an acidic environment, and rolling workability did not obtain good results.
[0141] Figure 3 The scatter plot shown in the figure shows the relationship between [Fe] + [Ni] + 2 × [Zn] and weak acid solubility (μg / mm 2 ) relationship. Figure 4 The scatter plot shown in Figure 2 shows the relationship between [Zn] and uniform solubility (μm).
[0142] When comparing the aluminum alloy foil of the embodiment with the aluminum alloy foil of the comparative example, it can be seen from Tables 1, 2 and Figure 3 ,4 It can be seen that in order to obtain a chemical solubility (dissolution loss per unit surface area) of 2.8 μg / mm in a weakly acidic environment, 2 As mentioned above, for an aluminum alloy foil having uniform solubility in an acidic environment (maximum height roughness Sz after acid treatment) of 7.1 μm or less and an evaluation of rolling workability of "A", "B" or "C", [Zn] is required to be greater than 0.4 and less than 5.1, [Fe] + [Ni] is greater than 0.4 and less than 4.8, and [Fe] + [Ni] + 2×[Zn] is greater than 2.5.
[0143] Based on the measurement results of the natural potential and cathode polarization curve corresponding to the Zn solid solution content in the aluminum alloy foil shown in Table 3, it can be considered that if Fe, Ni and Zn are added to the aluminum alloy and [Zn], [Fe] + [Ni] and [Fe] + [Ni] + 2×[Zn] are controlled, the potential of the aluminum parent phase can be lowered and the potential of the second phase particles distributed in the aluminum alloy foil can be increased. As a result, the chemical solubility and uniform solubility of the aluminum alloy foil are improved.
[0144] In addition, it can be seen from Tables 1 and 2 that in order to obtain the above-mentioned aluminum alloy foil with excellent chemical solubility in a weakly acidic environment, uniform solubility in an acidic environment and rolling processability, it is preferred that at least the Fe content is greater than 0.0001 mass % and less than 3.1 mass %, the Ni content is greater than 0.0001 mass % and less than 3.0 mass %, and the Zn solid solution amount is preferably greater than 0.3 mass % and less than 4.1 mass %, and the inevitable impurities include one or more elements selected from the group consisting of Si, Mn, Mg, Cu, In, Sn, Na, V, Ti, Zr, Cr, B, Ga, Bi, Pb, Sb and As. It is preferred that the total content of the one or more elements is less than 0.6 mass %, the Mn content is less than 0.4 mass %, and the Mg content is less than 0.4 mass %. Except for Mn and Mg included as inevitable impurities, the content of each of the above elements is preferably less than 0.2 mass %.
[0145] In addition, it can be seen from Tables 1 and 2 that the area occupancy of second phase particles with an equivalent circle diameter of 0.1 μm or more distributed on the surface of the aluminum alloy foil is preferably 1.7% or more, and the area occupancy of second phase particles with an equivalent circle diameter of 3.0 μm or more distributed on the surface of the aluminum alloy foil is preferably 2.0% or less.
[0146] <How to use>
[0147] The aluminum alloy foil developed by the present invention has excellent chemical solubility in weak acid environments and uniform solubility in acidic environments, so it can fully exert its effect in fields requiring the use of etching treatment liquids with less environmental burden, especially as a substrate for etching treatments aimed at forming special fine surfaces. In addition, since it also has excellent chemical solubility in strong acid environments, it can improve the processing efficiency of existing etching treatments and also help reduce the amount of etching treatment liquid used.
[0148] The aluminum alloy foil of the present invention can also be formed into a laminate by laminating a resin film layer and / or a coating layer on one or both sides thereof according to the application. In this case, the laminate using the aluminum alloy foil of the present invention has the above-mentioned excellent properties such as high chemical solubility, so the surface treatment for the purpose of improving the adhesion and the etching treatment for processing into the desired shape can be treated using a weak acid. Therefore, the laminate using the aluminum alloy foil of the present invention can be manufactured by a manufacturing method with a smaller environmental burden. In addition, the laminate using the aluminum alloy foil of the present invention is also easy to dissolve in the laminate when it is discarded, so it is also very easy to separate the resin film layer for recycling.
[0149] Description of Reference Numerals
[0150] 1a, 1b, 1c, 1d: aluminum alloy foil
[0151] 2a, 2b, 2c, 2d: Aluminum parent phase
[0152] 3a, 3c: Second phase particles with equivalent circle diameter of 0.1 μm or more
[0153] 4b, 4d: Second phase particles with equivalent circle diameter of 3.0 μm or more
Claims
1. An aluminum alloy foil containing Fe, Ni and Zn, with the balance consisting of Al and unavoidable impurities, characterized in that: When the contents of Fe, Ni and Zn in the aluminum alloy foil are represented by mass % as [Fe], [Ni] and [Zn], respectively, [Zn] is 0.4 or more and 5.1 or less, [Fe] + [Ni] is 0.4 or more and 4.8 or less, and [Fe] + [Ni] + 2× [Zn] is 2.5 or more.
2. The aluminum alloy foil according to claim 1, characterized in that [Fe] is 0.0001 or more and 3.1 or less, and [Ni] is 0.0001 or more and 3.0 or less.
3. The aluminum alloy foil according to claim 1, characterized in that Zn is contained as a solute element, and the amount of Zn solid solution is 0.3 mass % or more and 4.1 mass % or less.
4. The aluminum alloy foil according to claim 1, characterized in that The unavoidable impurities include one or more elements selected from the group consisting of Si, Mn, Mg, Cu, In, Sn, Na, V, Ti, Zr, Cr, B, Ga, Bi, Pb, Sb and As, and the total content of the one or more elements is less than 0.6 mass%.
5. The aluminum alloy foil according to claim 4, characterized in that The content of Mn is 0.4 mass % or less, and the content of Mg is 0.4 mass % or less.
6. The aluminum alloy foil according to claim 1, characterized in that The area occupancy of the second phase particles having an equivalent circle diameter of 0.1 μm or more distributed on the surface of the aluminum alloy foil is 1.7% or more.
7. The aluminum alloy foil according to claim 6, characterized in that The area occupancy of the second phase particles having an equivalent circle diameter of 3.0 μm or more distributed on the surface of the aluminum alloy foil is 2.0% or less.
8. The aluminum alloy foil according to claim 7, characterized in that The thickness is 5 μm or more and 300 μm or less.
9. A laminated body, characterized in that: A resin film layer and / or a coating layer is laminated on one or both surfaces of the aluminum alloy foil according to any one of claims 1 to 8.
10. A method for producing an aluminum alloy foil, characterized in that: The following processes are available: A process for preparing a molten aluminum alloy, wherein the molten aluminum alloy contains Fe, Ni and Zn, and the balance contains Al and inevitable impurities, wherein the contents of Fe, Ni and Zn in the molten aluminum alloy are [Fe], [Ni] and [Zn] respectively in mass %. Adjust [Zn] to 0.4 or more and 5.1 or less. Adjust [Fe] + [Ni] to 0.4 or more and 4.8 or less, and Adjust [Fe] + [Ni] + 2 × [Zn] to 2.5 or more; A casting step of casting the molten metal to obtain a casting body; In the rolling step, the cast body is cold-rolled to obtain an aluminum alloy foil.
11. A method for producing a laminate, characterized in that: The following processes are available: A step of preparing an aluminum alloy foil obtained by the manufacturing method according to claim 10; A lamination step of laminating a resin film layer and / or a paint layer on one side or both sides of the aluminum alloy foil.
Citation Information
Patent Citations
Aluminum foil for printed circuit
JP2008121090A